Impact of mAb-FcRn affinity on IgG transcytosis across human well-differentiated airway epithelium - Togami, Kohei; Wolf, Whitney; Olson, Lucas C.; Card, Madison; Shen, Limei; Schaefer, Alison; Okuda, Kenichi; Zeitlin, Larry; Pauly, Michael; Whaley, Kevin; Pickles, Raymond J.; Lai, Samuel K. (Frontiers in Immunology, 2024)
Effective treatment and immunoprophylaxis of viral respiratory infections with neutralizing monoclonal antibodies (mAbs) require maintaining inhibitory concentrations of mAbs at the airway surface. While engineered mAbs with increased affinity to the neonatal Fc receptor (FcRn) are increasingly employed, little is known how increased affinity of Fc to FcRn influences basal-to-apical transepithelial transport (transcytosis) of mAbs across the airway epithelium. To investigate this, we utilized a model of well-differentiated human airway epithelium (WD-HAE) that exhibited robust FcRn expression, and measured the transepithelial transport of a mAb against SARS-CoV-2 Spike protein (CR3022) with either wildtype IgG1-Fc or Fc modified with YTE or LS mutations known to increase affinity for FcRn. Despite the marked differences in the affinity of these CR3022 variants for FcRn, we did not find substantial differences in basal-to-apical transport reflective of systemic dosing, or apical-to-basal transport reflective of inhaled dosing, compared to the transport of wildtype IgG1-Fc. These results suggest increasing FcRn affinity may only have limited influence over transcytosis rates of systemically dosed mAbs across the human airway epithelium over short time scales. Over longer time scales, the elevated circulating levels of mAbs with greater FcRn affinity, due to more effective FcRn-mediated recycling, may better resupply mAb into the respiratory tract, leading to more effective extended immunoprophylaxis.